Biographical Files on Stalin, Tito, Brezhnev and Gorbachev
The series contains news agency releases, transcripts of the monitopring of the broadcasts of the Czechoslovak Radio and Television (and Radio Moskva Czech and Slovak broadcasts), articles from RFE and RL publications, transcripts of Brezhnev's speeches, newspaper issues, A and B wires, coverage of Brezhnev's visit in USA and Gorbachev's visit in Czechoslovakia. The files are are useful cross-references to the USSR Biographical File and theYugoslav Biographical File.